N1
log 7 (2 - x) =< log 7 (2x^2 - x)
2 - x =< 2x^2 - x
2x^2 - 2 >= 0
x € (-беск. ; -1] U [1 ; +беск.)
N2
log 0,5 (x^2 - 1) < -3
log 0,5 (x^2 - 1) < log 0,5 (8)
x^2 - 1 > 8
x^2 - 9 > 0
x € (-беск. ; -3) U (3 ; +беск.)
N3
lg (7^(6 - 2x) + 3) - lg (39) > lg (4) - lg (3)
lg (7^(6 - 2x) + 3) > lg (39) + lg (4) - lg (3)
lg (7^(6 - 2x) + 3) > lg (52)
7^(6x - 2) + 3 > 52
7^(6x - 2) > 49
6x - 2 > 2
6x > 4
x > 2/3
N4
log 2x + 1 (5 - 2x) > 1
log 2x + 1 (5 - 2x) > log 2x + 1 (2x + 1)
5 - 2x > 2x + 1
- 4x > - 4
x < 1
log 2x + 1 (5 - 2x) > 1
log 2x + 1 (5 - 2x) > log 2x + 1 (2x + 1)
5 - 2x < 2x + 1
-4x < -4
x > 1
2x + 1 > 0
x € (-1/2 ; 0)
5 - 2x > 0
x € (0 ; 5/2)
{x € (-1/2 ; 0) x - не существует
{x > 1
{x € (0 ; 5/2) x € (0 ; 1)
{x < 1
ответ : (0 ; 1
2x+x=5+7
3x=12
x=12/3
x=4
2)x(x+5)=-6
x^2+5x=-6
x²+5x+6=0
D=25-4*1*6=25-24=1
-5+1
x1==-4/2=-2
2
-5-1
x2==-6/2=-3
2
ответ:-3;-2
3)x²=0
x=0
ответ:0
4)3(1-x)+(x-2)-x=3-3x+x-2-x=-3x-1
5)5n-3(n+2)+(n-6)=5n-3n-6+n-6=3n-12=3(n-4)
6)m-(2m-6)+3(m-3)=m-2m+6-3m-9=-4m-3
7)2(3x+1)-(x-2)-3x=6x+2-x+2-3x=2x+4=2(x+2)